Analisis Kemampuan Siswa dalam Belajar Sejarah di SMA N 2 Padang - Sari Anggraini; Ridho Bayu Yafterson (Departement of Mathematics Education, 2023)
The purpose of this study is to determine the ability of students' understanding in learning history. Ability analysis was carried out due to the low understanding of students' learning towards history lessons and the low student achievement in history lessons. The study was conducted at SMA Negeri 2 Padang class XE1. This study uses a qualitative descriptive study method. To obtain information, researchers made direct observations. The results of this study stated that the ability to understand history learning material was needed by students, but the activity of the percentage of students who did not meet the criteria became an obstacle. Therefore it takes students' ability to understand the material through activities that can be done by students. With no internet access and can be on all student and teacher smartphone devices. The ability to understand learning is expected to increase enthusiasm for learning and student achievement.